A Case of Juvenile and Adenomatous Polyposis Associated with Telangiectasia and Colonic Carcinoma - Z. MUNGAN; N. EROL; G. BOZTAŞ; C. ULAŞOĞLU; O. ÇUBUKCU; R. ERDOĞAN; R. SEZER (Turkish Journal of Gastroenterology, 2020)
-